ANALISIS POTENSI DAN TANTANGAN IMPLEMENTASI CHROMEBOOK SEBAGAI MEDIA ASESMEN DIAGNOSTIK DI SEKOLAH DASAR KECAMATAN WATUKUMPUL KABUPATEN PEMALANG - Iman Triyogi; Munadi; Paridjo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the potential and challenges of implementing Chromebooks as a medium for diagnostic assessment in elementary schools in the Watukumpul District, Pemalang Regency. Employing a qualitative case study approach, the research was conducted at two schools: SD Negeri 03 Watukumpul and SD Negeri 01 Cawet. Data collection techniques included in-depth interviews, observation, and documentation. The participants consisted of two principals, four teachers, and twenty students. The results show that Chromebooks have positive potential to enhance the effectiveness of diagnostic assessments, especially in identifying learning gaps quickly and interactively. However, several challenges arise, such as limited digital competence among teachers, unstable internet connectivity, and technical issues in device operation. This study recommends intensive teacher training and infrastructure improvements to optimize Chromebook utilization in elementary education.